Right To Health Protection in the Former-Soviet Constitutions: Constitutional and Legal Analysis - Maksakova Ruslana1, Yurii Viktorovych Kyrychenko2, Maryna Leonydovna Smoliarova3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The constitutional framework for legal aid to available health care therefore determines one of the strategicareas of policy of democratic, social and law-governing states (former Soviet states). This determines therelevance of studies of resistance to constitutional and legal regulation of the health system formed as a resultof changes in the skin and radical structure of social structure in previous USSR states. The article containsthe constitutional and legal analysis of the right to health protection in the former-Soviet constitutions byreviewing the constitutional healthcare provisions and specifying the groups of qualified bearers of right tohealth protection and variety of rights as the healthcare system elements. The studies are to be continued,as well as the review and summary of information about constitutional and legal regulation of the right tohealth protection in the former-Soviet states are needed.